Analisis Nilai Multikulturalisme dalam Kurikulum Fiqih Madrsah Aliyah - Zuhriati; Meyniar Albina (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to analyze the multicultural values embedded in the fiqh curriculum at Madrasah Aliyah. As a key component of Islamic education, fiqh plays an essential role in shaping students' attitudes and behaviors toward cultural, ethnic, and religious diversity. By incorporating values of tolerance, respect for differences, and promoting harmonious coexistence in a plural society, fiqh can contribute to fostering a more inclusive worldview among students. The research utilizes a qualitative approach, specifically content analysis, to examine the fiqh curriculum documents implemented in Madrasah Aliyah across various regions. The findings reveal that the curriculum includes several multicultural values, such as the importance of respecting diversity and promoting peaceful coexistence. However, the study also identifies areas where the implementation of these values could be strengthened, particularly in the alignment of teaching materials with the realities of a multicultural society. Furthermore, there is a need for more contextual and interactive teaching methods to enhance students’ engagement with these values. This research offers recommendations for the further development of the fiqh curriculum, aiming to make it more responsive to the dynamic multicultural landscape in Indonesia. The findings contribute to the broader discourse on integrating multicultural education into religious studies, providing insights for educators and policymakers.